Metal Halide Perovskite Nano/Microwires. Issue 1 (20th November 2021) - Wang, Meng; Cao, Fengren; Li, Liang
Abstract : Metal halide perovskite nano/microwires (NMWs) are expected to serve as building blocks for next‐generation optoelectronic devices due to their attractive optoelectronic properties. The excellent performance of NMW‐based devices is mainly attributed to their well‐defined crystal structure, fewer grain boundaries, lower defect concentration, longer photocarrier lifetime, and confined carrier transport. To date, various methods (such as the template method, chemical vapor deposition, and solution method) have been developed to construct perovskite NMW‐based optoelectronic devices (including photodetectors, lasers, solar cells, and light‐emitting diodes. Although many breakthroughs have been achieved, it is still necessary to understand the underlying mechanisms and discover the internal relationship between NMW morphologies (including size, thickness, density, etc.) and optoelectronic properties to allow for broader applications for perovskite NMWs. This review summarizes the recent research on perovskite NMWs, especially synthesis strategies, unique characteristics, and optoelectronic applications, and provides some future perspectives for the practical application of perovskite NMW‐based devices. Abstract : Metal halide perovskite nano/microwires (NMWs) are expected as the building blocks for next‐generation optoelectronic devices. Their well‐defined crystal structure, fewer grain boundaries, lower defect concentration, longer photocarrier lifetime, and confined carrier transport endure them a great potential in further application. This review summarizes the recent research on perovskite NMWs, especially synthesis strategies, unique characteristics, and optoelectronic applications, and provides some future perspectives for the practical application of perovskite NMWs.